The Effect of CER, ALR and Exchange Rate Risk Management on Conventional Bank Profitability for the Period 2019 - 2022 - Sukartaatmadja, iswandi; Widhiacahyani, Andiko Pramestya Regita; Pramiudi, Udi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
A banking institution is one of the organizations that plays a very important role in the economy of a bangking country in performing the function the requires capital to finance banking activities. In addition to promoting the country’s economy, banks must also have a certain level of profit for sustainable development bank information.The purpose of the study is to investigate the effect of Cost Efficiency Ratio (CER), Average Lending Rate (ALR), and Exchange Rate (ER) on profitability by calculating Return On Asset (ROA) in conventional banks in the period 2019 – 2022. The data type used in this study is secondary data obtained from annual reports published on the BEI website and other sources official website of 40 (forty ) common banks. The testing method used in this study are descriptive analysis and classical hypothesis testing, including normality test, multicollinearity test, variable variance test and autocorrelation test. Then, by testing the hypothesis in this study using partial test )t-test), concurrent test (f-test), and deterministic analysis (r 2 – test), chow test, hausman test, and lagrange multiplier test. Keywoards : Cost Efficiency Ratio, Average lending Rate, Exchange Rate and Return On Asset